The Path to Establishing an Antitrust Regulatory System for Self-preference of Digital Platforms - Liu, Shining (International Journal of Social Sciences and Public Administration, 2024)
China's Anti-Monopoly Law currently fails to adequately cover the circumscribed regulation of self-preferential behavior on digital platforms. There are controversies in the academic circle about the definition of the illegality of digital platform self-preference. The purpose of this paper is to provide an institutional supply for the regulation of self-preference on digital platforms and to construct a localized system of self-preference on digital platforms through empirical research and comparative law study. Through the idea of "clear entry into the law - entry into the expansion - justified exemption", it defines, judges the illegality and regulates the self-preferential behavior of digital platforms, and explores the concise analysis path of anti-competitive behavior of digital platforms. It also explores the concise analysis path of anti-competitive behavior of digital platforms.